Pengaruh Soft Total Quality Management terhadap Kinerja UKM di DKI Jakarta: Pendekatan Balanced Scorecard - Zihni, Aufa Yarzqi; Arif, Helman (Jurnal Manajemen dan Usahawan Indonesia, 2023)
This study aims to analyse the effect of Soft Total Quality Management (Soft TQM) on SME performance in Jakarta, both from financial and non-financial perspectives. We used a balanced scorecard (BSC) approach and collected 135 datasets through online surveys to the business owners/manager. Data analysis was carried out by Structural Equation Modelling (SEM) method. The results of the data analysis showed that soft TQM has a negative and not significant effect on SMEs financial perspective, however there is a positive and significant effect on SMEs non-financial perspective. This study also discovered that innovation and leaning perspective mediates the impact of soft TQM on financial perspective in a positive and significant way.